Presentation zen design : simple design principles and techniques to enhance your presentations - Reynolds, Garr (Voices that matter, 2010)
"In his internationally acclaimed, best-selling book 'Presentation Zen: Simple Ideas on Presentation Design andDelivery', presentation master Garr Reynolds gave readers the framework for planning, putting together, and delivering successful presentations. Now, he takes us further into the design realm and shows how we can apply time-honored design principles to presentation layouts" -- Cover, p. 4